Vocal Fold Reconstruction Using an Autologous Pedicled Fat Flap in a Rabbit Model. (29th November 2019) - Lee, Seungwon; Seon, Sangwoo; Park, Kinam; Ryu, Junsun
Abstract : Objectives/Hypothesis: We evaluated the efficacy of a vocal fold reconstruction technique using a vascularized autologous pedicled fat (PEFA) flap in a rabbit model of vocal fold paralysis. Study Design: Animal model. Methods: The study included 30 male New Zealand White rabbits; 20 received vocal fold reconstructions (PEFA group) and 10 served as normal controls (control group). The right recurrent laryngeal nerve was resected, and simultaneous PEFA flap reconstruction was performed. The PEFA flap, including a pre‐epiglottic fat and thyroid perichondrium, was elevated and implanted through a window at the inferior border of the thyroid cartilage. Histological and high‐speed video analyses of vocal fold vibration were performed 1 month after PEFA reconstruction. The maximum amplitude of vocal fold vibration and the dynamic glottal gap were used to assess vocal fold vibration. Results: The histological findings showed that the lamina propria ratio (lamina propria pixels/total vocal fold pixels) and the total number of vocal fold pixels were similar between the PEFA and control groups. Vocal fold vibration analyses indicated that the maximum amplitude differences in the vibration were slightly lower in the PEFA group. However, the dynamic glottal gap of the vocal fold was not significantly different between the PEFA group and the control group. Conclusions: The PEFA flap vocal fold reconstruction technique maintained the vocal fold area without a significant reduction in vocal fold vibration in a rabbit model. Level of Evidence: NA Laryngoscope, 130:1770–1774, 2020